Influence of the cold sintering process and post annealing on the microstructure and Li-ion conductivity of LiTa2PO8 solid electrolyte. Issue 6 (15th March 2023) - Kim, Hyeonjin; Choi, Sinho; Peck, Dong-Hyun; Yoon, Seog-Young
Abstract: Recently, LiTa2 PO8 (LTPO) has attracted interest as a potential Li-ion solid electrolyte material because of its high bulk ionic conductivity and low grain boundary ionic conductivity. However, most ceramic-based solid electrolytes are fabricated via the high-temperature sintering process (typically above 1000 °C); such temperatures can cause the evaporation of Li from the compound. To replace high-temperature sintering of ceramics, the cold sintering process (CSP) was introduced; this process enables the densification of ceramics and composites at extremely low temperatures (below 300 °C). In this work, we investigate the effect of using the CSP and post annealing on the microstructure and Li-ion conductivity of LTPO pellets. It is found that the CSP pellets have an amorphous phase between particles. This intermediate amorphous phase creates a better contact between particles and is hypothesized to lead to more Li-ion migration paths. The CSP pellet is found to have a high density and high ionic conductivity of (1.19 × 10 −5 S/cm). The pellet obtained via the CSP has Li-ion conductivity similar to that of the pellet obtained via dry pressing after it has been annealed. The CSP pellet after post annealing shows good connections between particles and a high Li-ion conductivity of 1.05 × 10 −4 S/cm, which is comparable to the conductivity of a pellet obtained via high-temperature sintering. This work provides new evidence that the CSP is a promising alternative to high-temperature sintering for fabricating ceramic solid electrolytes.